Ph̄æn m̄æbot kānpatirūp rabop rātchakān, Ph̜̄o. S̜̄o. 2540-Ph̜̄o. S̜̄o. 2544 - W̨ōradēt Čhanthras̨ōn (Khana Kammakān Patirūp Rabop Rātchakān, Samnak Nāyok Ratthamontrī, 1997)
On civil service reforming plan, 1997-2001.